PERAN PENTING TEKNOLOGI INFORMASI DALAM MENDUKUNG PEMBELAJARAN JARAK JAUH DI MASA WABAH VIRUS COVID-19 - Tri Rizqi Ariantoro (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
In the current covid-19 pandemic, many schools and universities have started implementing distance learning, because the government itself has not confirmed when it will officially open schools offline or face to face in class, even though now some schools or universities have started holding classes in person or offline but must follow strict health protocols that meet covid-19 prevention standards. With a situation like today the role of information and communication technology is very important to connect teachers and learners in carrying out teaching and learning activities in distance learning. Distance learning is one of the adjustments in the education sector during the Covid-19 pandemic. In the implementation of distance learning, technology is the key to the continuity of distance learning which makes the learning process easier. Nowadays, there are many online platforms such as LMS (Learning Management System) as a support or means for teachers and learners to be able to provide and get learning resources. LMS (Learning Management System) is a software application for online activities, electronic learning, and training content